2009
DOI: 10.1093/humrep/dep065
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation in anandamide levels from ovulation to early pregnancy in in-vitro fertilization-embryo transfer women, and its hormonal regulation

Abstract: Our observations suggest that in successful pregnancy, a higher plasma AEA level at ovulation and a significantly lower level during implantation are required. The drop in AEA levels could be used as a biomarker for the appropriate timing of embryo transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 31 publications
6
56
0
1
Order By: Relevance
“…We reported that 2-AG induces a decrease in cytotrophoblast cell viability, through apoptotic cell death accompanied by an increase in reactive oxygen species (ROS) [1]. Placental endoplasmic reticulum (ER) stress and oxidative stress may be involved in the pathophysiology of intrauterine growth restriction and preeclampsia [2]. In this study, we investigate whether 2-AG effects involve activation of endoplasmic reticulum stress signaling pathways.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…We reported that 2-AG induces a decrease in cytotrophoblast cell viability, through apoptotic cell death accompanied by an increase in reactive oxygen species (ROS) [1]. Placental endoplasmic reticulum (ER) stress and oxidative stress may be involved in the pathophysiology of intrauterine growth restriction and preeclampsia [2]. In this study, we investigate whether 2-AG effects involve activation of endoplasmic reticulum stress signaling pathways.…”
Section: Discussionmentioning
confidence: 96%
“…Emerging lipid mediators, such as lipoxins (LXs) and resolvins (Rvs) are derived from various polyunsaturated fatty acids and possess potent anti-inflammatory properties. A LXs receptor has been cloned and denominated formyl peptide receptor like 1 (FPRL1/ALX), whereas Rvs may act on GPR18 or GPR32 [2]. These lipids are generated by cooperation between 5-lipoxygenase (LO) and 12-or 15-LO.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations